2019
DOI: 10.1051/e3sconf/201910502002
|View full text |Cite
|
Sign up to set email alerts
|

Physico-Chemical Properties of Soils in Lviv Volyn Coal Basin Area

Abstract: The results of the research showed that hydromorphous soils prevail on the territories adjoined to waste heaps. Swampy meadow and sod soils were defined. During investigation of swampy meadow soils it was determined that the soil is humused at a considerable depth. The soils are saturated with the bases. According to granulometric texture it is sandy loam soils, but with depth go to the middle loamy soils. The analysis for labile forms of heavy metals showed that in these soils the content of investigated heav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 3 publications
0
10
0
Order By: Relevance
“…They pollute almost all elements of the environment: air, ground water, land runoff, soil, plants. In this regard, we decided to investigate the toxicological composition of the dumps of mine # 9 "Novovolynska" and their on environmental impact [9]. Mine # 9 "Novovolynska" belongs to the State Enterprise "Volynvuhillya" and is located on the territory of Ivanychi region of Volyn region.…”
Section: Environmental Impact and Toxicological Properties Of Mine Dumps Of The Lviv-volyn Coal Basinmentioning
confidence: 99%
“…They pollute almost all elements of the environment: air, ground water, land runoff, soil, plants. In this regard, we decided to investigate the toxicological composition of the dumps of mine # 9 "Novovolynska" and their on environmental impact [9]. Mine # 9 "Novovolynska" belongs to the State Enterprise "Volynvuhillya" and is located on the territory of Ivanychi region of Volyn region.…”
Section: Environmental Impact and Toxicological Properties Of Mine Dumps Of The Lviv-volyn Coal Basinmentioning
confidence: 99%
“…A lot of research of the chemical content has been done, in particular in terms of heavy metals content in the territory of devastated landscapes, among which it is worth noting the studies that revealed significant differences in the toxicological composition of devastated landscapes in different places. In order to prevent the occurrence of waste water accumulations that are dangerous for the ecological state, it is necessary to use natural resources rationally, to carry out demineralization, reclamation and phytomelioration of disturbed lands in a timely manner (Bosak P. et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, due to the lost access to the main oil and gas fields on the Black Se a shelf and a significant part of the coal deposits in the Eastern Donbass, restructuring of mines and reducing the cost of produced coal is an extremely urgent and strategic task. The mining industry prospective development is impossible without the introduction of innovative technical and technological solutions: modern approach for mining field planning [3][4][5] backfilling of gob area [6][7][8][9], reclamation and recultivation processes [10][11][12], control of mine ventilation [13][14][15], geomechanical stydy of rock mass behaviour based on rock properties stydy [16][17][18][19], ecological and environmental management [20,21].…”
Section: Introductionmentioning
confidence: 99%